PO 34 - ANAFILAXIA AO ROCURÓNIO REVERTIDA COM SUGAMMADEX: UM CASO DE SUCESSO - Catarina Cruz Chaves1,; Maria Joana Almeida Garrett Tavares Guimarães1, (Journal of the Portuguese Society of Anesthesiology, 2023)
.